Effect of Temperature on Microstructure and Mechanical Properties of Superheater Steel Pipe in Thermal Power Plant - Nguyen, Thu Hien; Bui, Anh Thanh; Nguyen, Van Tan; Phung, Thi To Hang; Bui, Anh Hoa (Old Journal, 2018)
In thermal power plant, the failure of superheater steel pipe depends on working time, temperature and pressure of the steam. This paper presents an experimental investigation of the effect of heating temperature on microstructure and mechanical properties of the superheater steel (grade P22). The steel samples were cut from a new industrial pipe and heated to 500, 600 and 700 °C. The obtained results showed the distribution of ferrite and pearlite, a slight increase in the grain size and degradation of the strength as increasing the temperature. It was concluded that the temperature causes the microstructural change and decreasing strength of superheater pipe, resulting in damage of this part under long time service and high pressure of the steam.